PILGRIMAGE TOURISM IN UZBEKISTAN - To`xtasinova Gulsanam Alisher qizi; Abdurahmonov To'raxon (TADQIQOTLAR.UZ, 2024)
Abstract: Pilgrimage tourism in Uzbekistan offers a fascinating journey through the country's rich cultural and religious heritage. This article delves into the historical significance and spiritual allure of Uzbekistan's pilgrimage destinations, highlighting iconic sites such as Samarkand, Bukhara, and Turkistan. We explore the architectural marvels of Registan Square, the mausoleum of Imam al-Bukhari, and the ancient streets of Bukhara, which attract pilgrims and tourists alike. Additionally, we examine the economic and social impact of pilgrimage tourism on local communities, emphasizing the importance of preservation efforts and sustainable development practices. Through a blend of historical insights and contemporary perspectives, this article sheds light on the profound experiences and cultural exchanges that characterize pilgrimage tourism in Uzbekistan.